Novel Insights into the Pathogenesis of Hirschsprung's-associated Enterocolitis - Jiao, Chun-Lei; Chen, Xu-Yong; Feng, Jie-Xiong (Chinese medical journal, 2016)
Objective: To systematically summary the updated results about the pathogenesis of Hirschsprung's-associated enterocolitis (HAEC). Besides, we discussed the research key and direction based on these results. Data Sources: Our data cited in this review were obtained mainly from PubMed from 1975 to 2015, with keywords "Hirschsprung enterocolitis", "Hirschsprung's enterocolitis", "Hirschsprung's-associated enterocolitis", "Hirschsprung-associated enterocolitis", "HAEC", and "EC". Study Selection: Articles regarding the pathogenesis of HAEC were selected, and the articles mainly regarding the diagnosis, surgical approach, treatment, and follow-up were excluded. Results: Several factors, mainly including mucus barrier, intestinal microbiota, and immune function, as well as some other factors such as genetic variations and surgical reasons, have been found to be related to the pathogenesis of HAEC. Changed quantity and barrier property of mucus, different composition of microbiota, and an abnormal immune state work together or separately trigger HAEC. Conclusions: The maintenance of intestinal homeostasis is due to a well cooperation of microbiota, mucus barrier, and immune system. If any part presents abnormal, intestinal homeostasis will be broken. Meanwhile, for patients with Hirschsprung's disease or HAEC, dysfunction of these parts has been found. Thus, the happening of HAEC may be mainly attributed to the disorders of intestinal microbiota, mucus barrier, and immune system.